Production of Clarias gariepinus seeds through accelerated female broodstock rematuration - Prama Hartami; Mahdaliana Mahdaliana; Eva Ayuzar (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
This study aims to determine the effectiveness of Oodev and Turmeric flour on feed to accelerate the rematuration of female broodstock catfish for increasing seed production. Oodev hormone is believed to accelerate the maturation process of broodstock, while turmeric flour with its active ingredients can improve liver performance in the vitellogenesis process. The method was a non-factorial completely randomized design with 4 treatments and 3 replications. The treatments are Control, (A) Oodev 0.3 ml/kg of feed, (B) Turmeric flour 5 gr/kg of feed, and (C) Combination of Oodev + Turmeric flour. The results showed that C treatment was the best treatment which produced a GSI value of 14.57 2.53%, period of rematuration was 32.33 4.16 days, egg diameter was 1.27 0.12 mm, fecundity was 22,939.97 880.38 eggs/kg of broodstock weight, fertilization rate was 80.18 9.75%, hatching rate was 79.80 2.88%, and larval survival reached 83.17 9.69%. Meanwhile, the specific growth of seed length in all treatments had no significant effect between treatments. The results of this study will certainly provide useful information for increasing catfish seed production both in Aceh and on a Nationally. This acceleration of maturation also has a positive impact in maximizing the available broodstock without having to increase the number of catfish broodstock to produce seeds of superior quality and benefit the cultivators.Keywords:EnrichmentFemale BroodstockPerformanceRematurationReproduction